Selbsteinschätzung der Behandlungsdringlichkeit bei Vorstellung in einer neurologischen Notfallambulanz: Ergebnisse einer Patientenbefragung - Harenberg, Linda; Oßwald, Hanna; Jaschonek, Hannah; Nagel, Simon (Der Nervenarzt, 2019)
Background: The proportion of patients with neurological disorders as well as the absolute number of patients in German emergency departments is rising. Objective: This article presents the results of a survey among patients with self-referral to a dedicated neurological emergency department (ED). We sought to find out if the individual evaluation of urgency for treatment was comparable for patients and physicians. Methods: During a prospective trial to validate a new and specific neurological triage system over a time period of three months (October 2015 to January 2016), patients who presented themselves to the ED were handed a questionnaire and asked to provide information on the symptoms, including duration and the subjective urgency for evaluation by a physician (priority 1-4, 1 = emergency, 4 = elective). The results were descriptively evaluated and the subjective assessment of urgency was compared to the physicians’ evaluation. Results: From a total of 836 questionnaires, handed out to each patient with self-referral to the neurological ED, 528 (63%) were returned and analyzed. The most common symptoms were headaches, vertigo, paralysis and sensory deficits. In 24% of the patients the symptoms had lasted less than 24 h, while in 35% the symptoms had persisted for over 1 week. Over half of the patients (55%) indicated that the symptoms needed an emergency evaluation by a physician, while only 3% actually required immediate medical attention according to the retrospective assessment by physicians. This discrepancy was similar even after classification into symptoms and symptom duration. Only 2.6% of the patients stated that the reason for presenting to the ED was the inability to obtain an outpatient appointment. Discussion: Patients regarded their symptoms as being a medical emergency much more often than physicians did. This was independent of the symptoms and their duration. An objective triage for patients in an ED is necessary.
First Online: 01 October 2018
Gesehen am 20.09.2019